ANALISIS PROSES REKRUTMEN KARYAWAN DI HOTEL SHERATON BANDUNG - Muhamad Mukti Ali; Dicky Maryono (Economicus, 2024)
Recruitment is a process of searching for prospective employees who can meet the qualifications specified by the company. These prospective employees are also referred to as job applicants, individuals who aspire to work for a company. The recruitment process begins with the company seeking new employees and ends with the submission of applications. The result obtained is a collection of applicant data. The expected benefit is effective recruitment. In an effective recruitment process like this, the more applicants there are, the more selective the recruitment process conducted by the company. This study aims to analyze the recruitment process conducted by the human resource department at hotel sheraton bandung. The objectives of this recruitment process analysis are: a). To determine the recruitment system used by hotel sheraton bandung. B). To understand the employee recruitment process applied at hotel sheraton bandung. Using qualitative methods and data collection through interviews, observations, and document reviews. This results in qualitative data in the form of written and spoken words from the interviewees. The results of the research indicate that the recruitment process still does not yield satisfactory outputs, such as errors that may be made by applicants or hr. Factors include applicants' lack of diligence in applying. The solution to this case is to identify the problems faced when applying through web-based job vacancy platforms.